There and back again: A simple theory of planned return migration - Florian Knauth; Jens Wrona (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2018)
We present supportive empirical evidence and a new theoretical explanation for the negative selection into planned return migration between similar regions in Germany. In our model costly temporary and permanent migration are used as imperfect signals to indicate workers' high but otherwise unobservable skills. Production thereby takes place in teams with individual skills as strategic complements. Wages therefore are determined by team performance and not by individual skill, which is why migration inflicts a wage loss on all workers, who expect the quality of their co-workers to decline. In order to internalise this negative migration externality, which leads to sub-optimally high levels of temporary and permanent migration in a laissez-faire equilibrium, we propose a mix of two policy instruments, which reduce initial outmigration while at the same time inducing later return migration.
Keywords: R23; J61; D82; 330; return migration; signalling; selection; strategic complementarity